A case of severe preeclampsia presenting as acute pulmonary oedema - Sumangala Devi, D.; Vijay Kumar, Bindu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Pulmonary edema refers to an excessive accumulation of fluid in the pulmonary interstitial and alveolar spaces. It may occur in low risk pregnancies but one very important predisposing factor is association with preeclampsia. We are reporting a case of severe preeclampsia presenting as acute pulmonary oedema. 21 year old primi, a known case of gestational hypertension on drugs had pedal edema which was progressively increasing. She was admitted at 29w5d as her BP was still high. Since her preeclampsia profile was normal and her BP was controlled she was continued on conservative management. After 2 days she developed cough, tachypnoea and tachycardia with clinical findings suggestive of A/c pulmonary oedema. Shifted to HDU and started on diuretics and other symptomatic management. After 1 hour as patient’s condition was worsening with O2 saturation fall, decided for LSCS + elective post operative ventilatory support. LSCS done showed evidence of Grade 3 abruption with couvelaire changes on uterus. Baby weighed 1.24 kg, severely asphyxiated, died after 3 days. Patient was put on ventillatory support and she improved postoperatively. Acute pulmonary oedema in pregnant women is a life-threatening event. Prompt diagnosis and management is very important for the survival of the patient.